DOES INTERNAL CONTROL AFFECT THE QUALITY OF FINANCIAL REPORTING? - Tandayu, Reynard; Rapina, Rapina (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Mistakes in financial reporting are still a phenomenon that has occurred to date. Internal control is one component that can influence the quality of financial reporting. However, based on the results of previous research, there is still inequality, which is what motivates this research. This research aims to find out whether internal control influences the quality of financial reporting. This research uses a purposive sampling method. The sample in this study was 70 financial employee respondents who worked in the service, manufacturing, finance, and health industries””hypothesis testing using SEM PLS. The research results show that internal control influences the quality of financial reporting. This research contributes to enriching the literature and contributes to companies improving and maintaining internal control so that they can produce good quality financial reporting.